HOBBITS AT THE GATE OF EUROPE. POSTMODERNIST GEOPOLITICS IN ARTUR KLINAU’S NOVEL PICKELHAUB - Kawalou, Siarhiej (Porównania, 2012)
The article considers an interesting tendency of contemporary Belarusian prose: artistic adoption of the European geographical space, transfer of actions and narration from Minsk to cafés of Warsaw and clubs of Berlin. The vivid manifestation of this tendency is a new novel of a famous avant-garde artist and experimental writer Artur Klinaŭ Pickelhaube (2011). The author of the article investigates the matter how the expansion of the geographical borders influences the artistic peculiarities of the novel. The researcher thinks that the main value of the novel is a particular sometimes unusually ironic interpretation of the national self-identification, Belarus’s searches of its place in Europe, perception of the Belarusians by other Europeans.